A fan studies primer : method, research, ethics - Booth, Paul, 1981-; Williams, Rebecca, 1981- (Fandom & culture., 2021)
"The discipline of fan studies is famously undisciplined. But that doesn't mean it isn't structured. A Fan Studies Primer: Methods, Research, Ethics will be the first comprehensive primer for classroom use that shows students how to do fan studies, in practical terms. The expansion of fan studies as an academic field and the growing visibility of fandom and fan activities in popular culture have led to more instructors using students' fandom in the classroom, and teaching fan studies as a disciplinary focus. Teaching fandom and fan studies means drawing from a multidisciplinary spectrum of methodologies and foci. Yet, as fan studies itself is often a "moving target," it is imperative to have a volume that approaches the various contributions, methodologies, ethics, and lacunae of the field in a classroom setting. With contributions from many of the biggest names in fan studies, co-editors Paul Booth and Rebecca Williams pull together case studies that demonstrate the wide array of methodologies available to fan studies scholars, such as auto/ethnography, immersion, interviews, online data mining, historiography, and textual analysis. They also probe the ethical questions that are unique to fan studies work and that continue to crop up as the field develops, such as use of online fan content for research, interview methods, consent, and privacy. Both experienced scholars and new students alike will find a useful overview of the diverse research topics in fan studies, whether it's Harry Potter, superheroes, or celebrities, as well as a catalog of conscientious and effective techniques for those who want to join in"--